POTENSI ANTIBODI SPERMATOZOA TERHADAP SPERMATOGENESIS DAN FERTILISASI PADA TIKUS PUTIH - Indah Norma Triana (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2007)
The experiment was conducted the potential of antiibody sperm to spermatogenesis and fertility of the male rat. Ten of rat testis have been used in this research, then crushed and added with 10 cc saline and then were filtrated and centrifuged 1800 rpm for ten minutes. Twenty four of the male rat divided in to four groups. Group I: injected with saline 0.1 cc/sc/day for 45 days; group II: injected with testis suspension 0.1 cc/sc/day for 15 days; group III: injected with testis suspension 0.1 cc/sc/days for 30 days; group IV: injected with testis suspension 0.1 cc /sc/days for 45 days. Then each of the male rat were mated with female, then the number of the total of pups were counted. Male rat were killed and testis were collected for preparation of histology and count of the spermatocyte and spermatid. The results show that the number of the spermatocyte and spermatid has significant different in the group and control (p < 0.05). The number of the pups significantly different in the group and control (p < 0.05). Implication of this research was injected Antibodisperm on male rat can decrease of the number of spermatocyte, spermatid and the number of the pups.